Representation of Female Actors from the Perspective of Female Writers in the Novel â€œHati Suhitaâ€ - Mariyani, Anik; Sari, Esti Swatika; Liliani, Else (Indonesian Journal of EFL and Linguistics, 2024)
Novels are one of the literary discourses that impact the field of literacy today. This is caused by the value content contained in the novel. The value content infused through the novel will indirectly provide learning and new perspectives for the reader. The novel written by the writer with an Islamic boarding school background, Khilma Anis, entitled Hati Suhita is an example of a novel with values that have an impact on the point of view and mindset regarding the position and representation of women, especially from the perspective of a female writer. This novel brings an interesting theme in the critical discourse analysis model of Sara Mills. This research focuses on the position and representation of women in the novel. This research method uses qualitative research. The data used is in the form of novel manuscripts. Data collection techniques through reduction, data display, and verification. The results of the analysis show that the dominance of women as objects (position and representation of women) is dominated through 8 elements, namely 5 elements of critical discourse analysis at the phrase/sentence level (Metaphor, Transitivity system, Proverb, Feminism and Ideology, and Jokes and humor) and 3 elements at the discourse level (fragmentation, focalization, role).